Teleassessment can overestimate the risk of learning disability in first and second grade of primary school - Stefania Fontolan; Sandro Franceschini; Marisa Bortolozzo; Linda Greta Dui; Simona Ferrante; Cristiano Termine (Italian Journal of Pediatrics)
Abstract Background Early administration of reading, writing and math standardised tests allows us to assess the risk of developing a learning disorder and to plan a specific intervention. The ease of access to technological tools and past pandemic restrictions have led to the abandonment of face-to-face assessment in favour of teleassessment methods. Although these kinds of assessments sometimes seem comparable in the literature, their equivalence is not clearly defined. The first aim of our research was to test the comparability of the two modalities using a complete battery of neuropsychological tests. Second, we addressed whether the administration order could influence performance. Methods Using a within-subject sample design, we compared face-to-face and teleassessment performance in reading, writing and math tasks in 64 children attending first and second year of primary school. Results Teleassessment scores were lower than face-to-face; math tests weighted on difference. Differences were mitigated by previous experience with face-to-face modality. Conclusions Although there was considerable overlap between the two administration methods, teleassessment could lead to overestimation of the risk for learning disorders.